2018
DOI: 10.1186/s40885-018-0094-4
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D deficiency and risk of cardiovascular diseases: a narrative review

Abstract: Vitamin D, a fat-soluble prohormone, has wide-ranging roles in the regulation of many physiological processes through their interactions with the vitamin D receptors (VDR). It plays a major role in bones and calcium metabolism. Vitamin D deficiency is not uncommon and it has been associated with many health-related issues, including skeletal and non-skeletal complications. The association of low vitamin D and cardiovascular diseases and risk factors has been explored in both animal and human studies. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 135 publications
1
124
0
12
Order By: Relevance
“…VDR null-mice exhibited increased concentrations of renin and angiotensin II leading to hypertension. In wild type mice, 1,25(OH) 2 D administration reduced the expression of renin [61,62]. Although the evidence from animal studies clearly links vitamin D to blood pressure, vitamin D supplementation studies on hypertension in humans yielded mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…VDR null-mice exhibited increased concentrations of renin and angiotensin II leading to hypertension. In wild type mice, 1,25(OH) 2 D administration reduced the expression of renin [61,62]. Although the evidence from animal studies clearly links vitamin D to blood pressure, vitamin D supplementation studies on hypertension in humans yielded mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D also functions in the regulation of the immune system and in the proliferation and differentiation of numerous cell types. Over the past two decades, laboratory and epidemiological studies have also suggested that low vitamin D status may be associated with a variety of health risks, including respiratory illnesses (infections and asthma), adverse pregnancy outcomes, and chronic diseases of adulthood, such as osteoporosis and cardiovascular disease . To date, clinical trials have contributed a limited amount of empirical evidence to support the beneficial effects of vitamin D, primarily on the risk of respiratory infections and some adverse pregnancy outcomes; however, there is limited evidence thus far from randomized clinical trials to support effects on health outcomes other than bone health …”
Section: Vitamin D Physiologymentioning
confidence: 99%
“…Vitamin D inadequacy, using the Institute of Medicine definition of a 25-hydroxyvitamin D [25(OH)D] concentration less than 20 ng/mL, affects almost 50% of adults in the United States, with higher prevalence in those with darker skin tones (1–3). Observational studies show associations between low vitamin D concentrations and numerous adverse health outcomes, including autoimmune diseases, migraines, hypertension, dyslipidemia, cardiovascular events, and cardiovascular mortality (1,3–9). These studies are supported by recent Mendelian randomization studies which provide evidence for a causal relationship between low vitamin D concentrations and increased risk of obesity, ovarian cancer, hypertension, lower cognitive function during aging, multiple sclerosis, and all cause and cancer mortality (1016).…”
Section: Introductionmentioning
confidence: 99%